Kajian Penerapan Mekanisasi Pertanian Berbasis Usaha Pelayanan Jasa Alat dan Mesin Pertanian (UPJA) untuk Sistem Produksi Padi di Kabupaten Banyumas, Purbalingga dan Banjarnegara - Aninda Ayu Arizka; Bambang Purwantana; Lilik Soetiarso (AGRITEXTS: Journal of Agricultural Extension, 2021)
The use of agricultural equipment and machinery is one way to increase the productivity and efficiency of farming. In order to accelerate the adoption of agricultural equipment and machinery as part of the application of agricultural mechanization, one of which is through the agricultural equipment and machinery service business/usaha pelayanan jasa alat dan mesin pertanian (UPJA). This study aims to analyze the application of agricultural mechanization, especially related to the use of equipment and machinery by UPJA for the rice production system in Banyumas, Purbalingga and Banjarnegara Regencies. Data were obtained, including the ownership of the equipment and machinery, the extent of coverage carried out by the UPJA, the cost of renting the equipment and machinery determined by each UPJA, and the costs incurred for the operation of the equipment and machinery in each UPJA. The results of the calculation of the working capacity of the hand tractor obtained an average of 0.07 ha hour-1. The lack of ability of equipment and machinery operators as well as the topography of the area and soil conditions are factors that affect the working capacity of the hand tractor in this study. UPJA which has a coverage area of more than the Break Event Point (BEP) value means that the UPJA has met the minimum area that must be processed to break even. The results of the calculation of the B/C ratio are that 9 UPJAs are feasible because the B/C ratio > 1 and 10 UPJAs are not feasible because of the B/C ratio < 1. UPJA whose business is not feasible is expected to improve the managerial and performance of UPJA.